Morphology and morphometric relationships for sagitta otoliths in Lutjanus argentiventris (Pisces: Lutjanidae) and Hyporthodus acanthistius (Pisces: Serranidae) from the Colombian Pacific Ocean - Vladimir Puentes, Paola Rojas, Giovanni Pavolini, Carlos F. Gutiérrez, Ángel A. Villa (Pontificia Universidad Javeriana, 2021)
Fish earstones, or otoliths, are inner ear structures that can be studied to determine a fish’s age and are a source of taxonomically informative data. In the present work, sagitta otoliths of the Yellowtail snapper (Lutjanus argentiventris) and the Red grouper (Hyporthodus acanthistius) were collected in the Colombian Pacific, and their key morphological features were studied. Otoliths of the Yellowtail snapper were distinctly concave by their distal surface, revealing features shared with species of its genus (Lutjanus). Red grouper otoliths were elliptic and compressed laterally by their proximal surface, bearing similarities to those of other Serranid species. Morphometric relationships between otolith size weight and whole fish size and weight were also studied. In Red groupers significant statistical morphometric relationships between otolith and body features were found via power regression models; successfully relating otolith length with total fish length, otolith weight with total fish length, otolith length with total fish weight, and otolith weight with total fish weight. No significant morphometric relationships were found for the Yellow snapper data. In both fish species, otolith transversal sections proved best to identify its internal features and to distinguish otolith growth rings, as a method for determining the specimen’s age.